The Potential of Sweet Potatoes As A Raw Material for Making Solid Soap - Hariyani, Septiana; Anggraeni, Mustika; Firdausiyah, Nailah; Sutikno, Fauzul Rizal; Sari, Kartika Eka; Nurlan, Rahmah Indah Permata; Rachman, Ryan Fadhilah; Yahya, Muhammad Kamil (TEKAD : Teknik Mengabdi, 2026)
Sweet potato, especially the purple variety, is a widely cultivated agricultural commodities known for its high antioxidant content, particularly anthocyanins and other bioactive compounds beneficial for skin health. While primarily consumed as food, sweet potatoes also hold potential for non-food applications, one of which is the production of natural-based solid soap. This study explores the potential of sweet potato extract as an active ingredient in solid soap production, evaluated through its physical, chemical, and functional properties. The method involves ethanol extraction of purple sweet potatoes, followed by a saponification process using NaOH concentrations ranging from 3.5% to 12.5%, combined with plant-based oils such as coconut oil, olive oil, and palm oil. The findings are expected to demonstrate that sweet potatoes offer more than just nutritional value, they can also serve as a natural, eco-friendly, and economically valuable component in the formulation of herbal solid soap.